Refining Our “CRAFT”: The Community Research Academy to Foster RepresenTation (CRAFT) Program - Mackenzie E. Fowler PhD; Oluseun Akinyele MPH; Francine Walton MPH; Rochelle Wallace MS; Stacey A. Ingram MEd; Yu-Mei Schoenberger PhD; Soumya J. Niranjan BPharm, MS, PhD; Ritika R. Samant MPH; Claudia Hardy MPA; Silvia Gisiger-Camata MPH, Pharm, RN; Timiya S. Nolan PhD, APRN-CRNP, ANP-BC, FAAN (Cancer Control)
Introduction Clinical research participation is under-represented among minoritized groups (eg, Black Americans) leading to suboptimal generalizability of findings and likely propagating inequities in cancer outcomes. Offices of Community Outreach and Engagement at comprehensive cancer centers establish bidirectional relationships between institutions and communities to facilitate catchment-concordant clinical research. We describe a program to educate and empower community health workers (CHWs) to act as clinical research advocates within their communities. Methods Academic and community stakeholders adapted existing evidence-based educational materials addressing importance of clinical research. The resulting program was entitled Community Research Academy to Foster RepresenTation (CRAFT). CRAFT is a 3-hour “train the trainer” session including introduction to clinical trials with “myth busters”, “Ask the Participant” panel, and hands-on experience finding a clinical trial. CRAFT was evaluated for acceptability, change in knowledge/perception, maintenance, and suggestions for curriculum improvement. Results Training was held in December 2023 with 21 CHWs, with a refresher training in July 2024 with 19 CHWs. At initial training, all participants reported ‘excellent’ or ‘good’ satisfaction with CRAFT. Results indicate 48% reported increased knowledge and 33% improved perception, and 21% demonstrated increased objective knowledge of clinical trials. At refresher training, 94% reported ‘excellent’ or ‘good’ satisfaction with CRAFT, 47% reported increased knowledge and 73% increased objective knowledge of clinical trials. Of those completing both sessions and all objective knowledge questions, 50% maintained or improved their score. Qualitative feedback indicated need for additional training (eg, more testimonials, more facts to supplement “myth busting”, more trainings, additional information on how to present to the public, and collaboration with academic health system staff during future CHW-facilitated programs). Conclusion CRAFT increased awareness, knowledge, and perception of clinical research among diverse CHWs with maintenance over time. Next steps include refining CRAFT, administering CRAFT to volunteer community health advisors, continuing evaluation, and sharing with other institutions.